20.9k views
2 votes
20. Solve 4 - 2(b - 6) = 12

b = 2

b = 12

b = -2

b = -10​

User Chiaro
by
5.7k points

2 Answers

1 vote

Answer:

b=2

Explanation:

4-2b-2*(-6)=12

4-2b+12=12

-12 -12

4-2b=0

+2b +2b

4=2b

:2 :2

b=4:2

b=2

User Purushotam Kumar
by
5.7k points
7 votes

Answer:

b=2

Option A is the correct option.

Solution,


4 - 2(b - 6) = 12 \\ or \: 4 - 2b + 12 = 12 \\ or \: 4 + 12 - 2b = 12 \\ or \: 16 - 2b = 12 \\ or \: - 2b = 12 - 16 \\ or \: - 2b = - 4 \\ or \: b = ( - 4)/( - 2) \\ b = 2

Hope this helps...

Good luck on your assignment..

User Stoney Eagle
by
6.4k points